AN ANALYSIS OF FIGURATIVE LANGUAGE IN WOTIK WAWI WATEN CEREMONY AT KOPONG VILLAGE - Elisabeth Jevani Alanti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
Figurative language is an interesting phenomenon to be studied and analyzed because it is one of the most arduous topics that literal language processing has to face and it is used in any form of communication. The aims of this study were to identify and analyze figurative language of wotik wawi waten ceremony. This research used descriptive qualitative research. The techniques of data collection used in this research were interview and study document. The result of this study shows that there are four types of figurative language found, they are simile, repetition, hyperbole, and symbol.